"Chemical" surgery in treating basal cell carcinoma in elderly. Issue 1 (16th October 2018) - Chiriac, Anca E.; Balan, Gheorghe G.; Pinteala, Tudor; Chiriac, Anca; Betiu, Mircea
Abstract: The incidence of basal cell carcinoma (BCC) has been increasing in the last decades due to population aging and precise diagnosis. The difficulty that physicians face frequently is related to the treatment decision for BCC; when treating BCC, correct and personalized choices must be taken into consideration by selecting from a large variety of therapeutic options such as: surgical excision ("the golden standard therapy"), electrodessication, cryosurgery, radiation therapy, laser, photodynamic therapy, curettage, topical treatment (imiquimod, 5‐fluorouracil, vismodegib), or combining different treatments. The present authors present series of cases of patients diagnosed with BCC, highlighting that "chemical surgery" using 70% trichloroacetic acid could be a valuable option in the treatment of nonaggressive BCC of the face.